Some new host records of meliola from India - A.N. THITE**, C.R. PATIL* and (Indian Phytopathology, 2002)
A total of 15 Meliola species on new hosts in India were recorded: M. rhois on mangoes; M. robisoniii on Entada rheedei; M. stephaniae on Cyclea peltata; M. gouniae on Zizyphus oenoplia; M. palawanensis on Canthium dicoccum; M. erithalidis on Canthium parviflorum; M. obtusa on Wenlandia tomentosa; M. aulliniae on an unidentified host; E. schimae on Gordonia obtusa; M. trichostroma on Syzygium; M. culebrensis on Carvia callosa; M. coilcicola on Canthium rheedei; M. cadigensis on Euoda lunu-ankenda;M. aethiops on Entada rheedei; and M. groteana on Embelia ribes.